Preventing 'A Virological Hiroshima': Cold War Press Coverage of Biological Weapons Disarmament. (2nd January 2016) - Balmer, Brian; Spelling, Alex; McLeish, Caitríona
Abstract : This article examines representations of biological weapons during a crucial period in the recent history of this form of warfare. The study draws on a corpus of newspaper articles from the US New York Times and the UK Times and Guardian written around the time of the negotiation period of the 1972 Biological Weapons Convention, the international treaty banning this form of warfare. We argue that a conventional discourse can be found wherein biological weapons are portrayed as morally offensive, yet highly effective and militarily attractive. Interwoven with this discourse, however, is a secondary register which depicts biological weapons as ineffective, unpredictable and of questionable value for the military. We finish with a somewhat more speculative consideration of the significance of these discourses by asking what might have been at stake when journalists and other writers deployed such differing representations of biological warfare.